Effects of processing parameters on microstructures and properties of TIG melted surface layer of steel - Mridha, Shahjahan; Dyuti, S. (Trans Tech Publications, Switzerland, 2011)
In order to modify surface structure titanium powder was preplaced on steel surface and melted under TIG (tungsten inert gas) torch in a pure nitrogen environment which formed a resolidified layer of around 1 mm thickness. The preplaced titanium powder content was varied between 1.3 and 1.8 mg/mm2 and melting was conducted with energy inputs of 324 J/mm to 540 J/mm. The modified surface layer was analyzed in terms of microstructure, hardness, surface defects such as cracks and pores. The resolidified layer consisted of dispersion of TiN, Ti2N and TiN.88 dendrites in a ferrite matrix containing titanium. The modified layer showed some defects when melting were performed with low energy inputs. A maximum surface hardness of around 2000 Hv was developed in most of the tracks and this hardness corresponds to high concentration of TiN dendrites within the modified layer.